Apakah Penjara Menjadikan Narapidana Remaja Berperilaku Agresif - Milda Yanuvianti; Sulisworo Kusdiyati; Anita Cameliana (SCHEMA (Journal of Psychological Research), 2011)
The presence of convicts (prisoners) in prisons tend to be associated with the growing likelihood of aggressive behavior of prisoners who have been previously owned. According Kornadt (1981), aggressive behavior occurs because the interaction of individual external factors, namely unpleasant condition with internal factors, namely the motive for aggression. The purpose of this study to describe the behavior of aggression and dynamics based on the concept of aggression proposed by Kornadt (1981). The subjects of this study was 30 teenagers who are prison inmates Rutan Kebon Waru, Bandung. Data obtained using measuring devices, such as: Behavior Aggression Questionnaire which is based on behavioral theory of aggression from Kornadt (1981), Aggression Questionnaire Motive System or SAS from Kornadt, and the results of semi-structure interviews to find out how the inmates live up to the negative affect felt. The results revealed that aggressiveness occurs in adolescent inmates Rutan Kebon Waru residents, Bandung. Aggressive behavior is triggered by negative affective appreciation, a sense of angry, disappointed, annoyed, sourced from a physical condition such as prisons: prisoners are cramped space, lack of ventilation, poor sanitation, to food menus that do not meet nutritional standards. Another source of negative affect comes from a fellow prisoner of mockery, extortion and subsequent negative penggencetan. Afek enable prisoners and the motive of aggression on aggressive behavior occurs, with the goal of a fellow prisoner. Form of aggressive behavior that most often arise and are mostly done is verbal aggression., physical aggression, while a smaller percentage of its appearance. This is presumably related to finding that the combination of motive system aggression in inmates of Rutan Kebon Waru Bandung, is specific, ie, although the motives of high aggression, but aggression is also high barriers. Cultural factors are suspected as a factor influencing the low behavioral aggression in adolescent inmates need to be further investigated.